Smart contracts on the blockchain – A bibliometric analysis and review - Ante, Lennart (Telematics and informatics, 2021)
•468 smart contract-related articles and their 20,188 references are analyzed.•A structured overview of research concerning smart contracts is obtained.•Six major streams of smart contract research are identified through factor analysis.•Paths for future research on smart contracts are outlined. Smart contracts are decentrally anchored scripts on blockchains or similar infrastructures that allow the transparent execution of predefined processes. Using smart contracts, business logic can be automated and assets such as money become programmable, which opens up previously inaccessible application potential. To date, smart contracts control billions in value. This paper analyzes 468 articles on the topic of smart contracts and their 20,188 references, providing a summary and analysis of the current state of research on smart contracts and identifying intellectual structures and emerging trends. Using exploratory factor analysis for co-citation analysis, six different strands of research are identified that concern technical, social, economic and legal disciplines: I) technical foundations, development and open questions of blockchain networks, II) blockchain and smart contracts for the Internet of Things, III) smart contract standardization, verification and security, IV) blockchain and smart contracts for the disruption of existing processes and industries, V) potentials and challenges of smart contracts, and VI) smart contracts and the law. The interrelations between these groups and individual high-impact publications are visualized using social network analysis. A structured overview of the main strands of research concerning smart contracts, their development over time, the relevance of smart contract platforms in research, and conceptual connections between publications and discourses is obtained. Based on the results, starting points for future research are derived, which offer researchers and practitioners a substantial basis for their work on smart contracts.